Ma’had Aly dan Persoalan Desain Pengembangannya : Belajar dari Ma’had Aly Miftahul Huda dan al-Hikmah - Asep Opik Akbar (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2021)
One of the milestones of pesantren development is Ma ’had Aly appearance. Ma ’had Aly (pesantren colledge) is a new phenomenon in the light of recent Islamic education. Ma ’had Aly is one of any achievements introduced by pesantren scholars to respond the crisis of ulama’s existence. In addition, Ma’had Aty attendance is critised to the Islamic university’s appearance that has not been maximizing it’s roles to indorcing Islamic education particularly related to developing Islamic traditional studies as well. So, the attendance is most part for improving the pesantren not only academic sphere but olso characterise capacity building. One of the main problem, as experienced by other educational institutions, is faced with Ma ’had Aly is management issues especially planning management. It’s generally caused by human resourse’s constraint in pesantren This paper deals with managing the two Ma ’had Aly: Ma ’had Aly al-Hikmah Brebes Central Java and Ma’had Aly Miftahul Huda Manonjaya Tasikmalaya West Java. Each of the both Ma’had Aly reprecents public and private Islamic educational institution After describing the managing both Ma’had Aly, the writer will give some suggestions for developing Ma'had Aly on the future. Kata kunci: Ma’had Aly, al-Hikmah, Miftahul Huda, Formal, Takhasus, Pengembangan.